The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1007/bf00922534
|View full text |Cite
|
Sign up to set email alerts
|

Attention and distractibility during reading in hyperactive boys

Abstract: Nonhyperactive and clinically defined hyperactive boys were administered reading tasks under "quiet" and "distracting" conditions. Hyperactive boys were less attentive to task relevant stimuli and more attentive to task irrelevant stimuli than their controls. Our results demonstrate that the previous findings of inattentiveness among hyperactive boys on laboratory tasks can be generalized to more typical school activities such as reading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…As well, cross-modal stimulation (added noise during visual tasks) apparently had no detrimental effects (e.g., Carrol et al, 1994). Finally, there was no loss in reading performance even when elementary-level students with ADD were observably "distracted" (i.e., looked more than their peers) in the presence of combinations of telephones ringing, calculator noises, lights, and oscilloscope patterns than during nonstimulating conditions (Bremer & Stern, 1976).…”
Section: Selective Inattentionmentioning
confidence: 89%
“…As well, cross-modal stimulation (added noise during visual tasks) apparently had no detrimental effects (e.g., Carrol et al, 1994). Finally, there was no loss in reading performance even when elementary-level students with ADD were observably "distracted" (i.e., looked more than their peers) in the presence of combinations of telephones ringing, calculator noises, lights, and oscilloscope patterns than during nonstimulating conditions (Bremer & Stern, 1976).…”
Section: Selective Inattentionmentioning
confidence: 89%
“…For example, Bremer and Stern (1976) reported that although the children with hyperactivity attended more than the nondisabled children to auditory distractors during a reading task, no significant differences in reading performance were found between the groups during the distraction condition. Zentall and Zentall (1976) found that on an "academically related performance task" (p. 694), a highstimulation condition consisting of auditory and visual distractors did not impair task performance.…”
mentioning
confidence: 99%
“…Reardon and Naglieri (1992) found that hyperactive children experience significant difficulty when required to formulate and monitor plan and strategies while inhibiting impulsive responses. Bremer and Stern (1976) examined the offtask behavior and reading performance of boys with and without hyperactivity under varying contextual conditions. They reported that a majority of hyperactive boys skipped one fourth of the reading material, presented with more efforts, and evidenced poorer reading comprehension than the readingmatched comparisons.…”
Section: Discussionmentioning
confidence: 99%